THE ROLE OF MULTILATERAL INSTRUMENTS AND ITS IMPACT ON WITHHOLDING TAX UNDER INDIAN TAXATION LAWS: A CRITICAL ANALYSIS OF INDIAN TAXATION TREATIES UNDER ECONOMIC GLOBAL SUSTAINABLE GROWTH (CAHIERS MAGELLANES-NS, 2024)
“Better business conduct leads to thriving global economy”.Multilateral Instruments are the Multilateral treaties that enable jurisdictions to swiftly modify their bilateral ta treaties to implement measures designed to better address multinational tax avoidance. These measures were developed as part of OECD/G20 Base Erosion and Profit Shifting (BEPS) project. India has manifested the role of Multinational agencies which aims to spur the economic development through alleviating poverty along with  preserving the environment by reducing carbon emissions and generating electric transmitting gadgets which accelerates high scale of Capital investment even in the foreign entities dealing with the gadgets of economic sustainability.Though Multilateral Development Bank (MDB) provides grant to fund projects that provides both social and economic development but still Indian MLIs face utmost challenges in hearing the bilateral tax treaties signed under OECD Model convention.Hence, this Article seeks to analyse how MLI overrides the global treaties that are treated as the throny problem for escorting the amount of tax from the global arena and highlighting the loopholes of the taxation treaties leading Tax evasion and Tax avoidance within the territory of India.